Aplicação do combustível derivado de resíduos (CDR) para otimizar o uso da palha de cana e casca de eucalipto como fonte de energia térmica - Gundim, Robmilson Simões (Universidade Federal de São Carlos, 2022)
Refuse derived fuel (RDF), characterized as part of municipal solid waste (MSW), is the leftover from the recycling process of waste not yet disposed of in landfills. The cement industry already uses RDF in natura as part of an alternative source of fuel to reduce CO2 emissions. The objective was to investigate the production of mixtures, through agglutination and/or extrusion of RDF with sugarcane straw and RDF with eucalyptus bark to optimize their energy use. Seven flakes-type treatments were produced through the extrusion process (granules of mixtures of RDF with undefined biomasses and formats): T1 (100% RDF), T2 (90% RDF and 10% bark), T3 (75% RDF and 25% bark), T4 (50% RDF and 50% bark), T5 (90% RDF and 10% straw), T6 (75% RDF and 25% straw) and T7 (50% RDF and 50% straw) and six pieces-like treatments (compacted material from mixtures of RDF with undefined biomass and formats), following the same proportions (from T2 to T7). The results showed that the density of the treatment produced in flakes format (RDF with straw) was approximately 10 times greater than RDF (in natura). The moisture of the flakes treatment (RDF with bark), compared to the bark, achieved a reduction of 83%. The higher heating value (HHV) of the treatment (RDF with bark) was 30% higher than the bark. The results indicated the real possibility of producing mixtures between RDF and biomass, by extrusion process. The result is a better quality solid fuel: more homogeneous, lower humidity, higher HHV and easier storage and handling.
Application of Refuse Derived Fuel (RDF) to optimize the use of sugarcane straw and eucalyptus bark as a source of thermal energy
Keywords: Biomassas; Cimenteira; Extrusão; Flakes; Pedaços; Misturas; Polímeros; Biomasses; Cement plants; Extrusion; Mixtures; Polymers; Pieces; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::APROVEITAMENTO DA ENERGIA; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::CONTROLE AMBIENTAL; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO::PROCESSOS DE FABRICACAO, SELECAO ECONOMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::ENERGIA DE BIOMASSA FLORESTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::CONTROLE DA POLUICAO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::LEGISLACAO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::LIMPEZA PUBLICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS::PROPRIEDADES FISICO-MECANICAS DA MADEIRA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::PRODUTOS NATURAIS